Progress Pride Committee (ACTRA National, 2023)
ACTRA National is proud to be launching the ACTRA National Progress Pride Committee. The inaugural Committee meeting took place on Friday, May 26th, 2023. Mandate The mandate of the committee is to address issues that impact the Queer ACTRA membership across the country, and to build a National community through the sharing of relevant information […]
Keywords: Bibliographie; Dans le rapport